Analisis Perbandingan Kinerja Keuangan Bank Syariah dan Bank Konvensional - Mustabsyirah Mustabsyirah; Askari Zakariah; Novita Novita (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to analyze and compare the financial performance of Islamic banks and conventional banks in Indonesia using library research methods. Data sources come from related literature such as scientific journals, articles, previous research reports, and relevant online sources. Bank financial performance is measured through several ratios including capital ratio (CAR), asset quality (NPL), liquidity (LDR), profitability (ROA and ROE), and efficiency (BOPO) which are calculated based on the bank's financial statements. The results of the analysis show that in general the financial performance of both types of banks is in a healthy condition and meets regulatory standards. However, there are differences in performance in several ratios individually. Conventional banks tend to have better performance in CAR, NPL, BOPO, and ROA ratios, indicating better capital quality, assets, operating costs, and profitability. Meanwhile, Islamic banks show better liquidity performance (LDR) and asset growth. However, the difference in performance is not yet fully statistically significant. In general, the financial performance of conventional banks is superior. However, the performance of Islamic banks also experienced an annual increase. To improve competitiveness, Islamic banks need to continue to make improvements, especially in terms of capital, cost management, credit quality, and increasing fee-based products. Both types of banks have developed and operated harmoniously without causing significant financial turmoil. The results of the study are expected to provide a stronger picture of the comparison of the financial performance of Islamic and conventional banks in Indonesia.